2013
DOI: 10.1002/jor.22411
|View full text |Cite
|
Sign up to set email alerts
|

Increasing both CoCrMo‐alloy particle size and surface irregularity induces increased macrophage inflammasome activation in vitro potentially through lysosomal destabilization mechanisms

Abstract: Recent investigations indicate that innate immune “danger-signaling” pathways mediate metal implant debris induced-inflammatory responses, e.g. NALP3 inflammasome. How the physical characteristics of particles, (size, shape and chemical composition) affect this inflammatory reactivity remains controversial. We examined the role of Cobalt-Chromium-Molybdenum (CoCrMo) alloy particle shape and size on human macrophage phagocytosis, lysosomal destabilization, and inflammasome activation. Round/smooth vs. irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 43 publications
3
99
0
3
Order By: Relevance
“…Under these conditions, inflammasome activity was clearly induced by apatite. Inflammasome activation by particles can be due to particle-induced reactive oxygen species and phagolysosomal destabilization [32][33][34] and, in some circumstances, lead to cell death. Incubation of mononuclear cells with apatite for long periods could therefore result in artefactual particle 'gorging', lysosomal disruption and cell death [2].…”
Section: Effect Of Resting Of Cells and Tcm Filtrationmentioning
confidence: 99%
“…Under these conditions, inflammasome activity was clearly induced by apatite. Inflammasome activation by particles can be due to particle-induced reactive oxygen species and phagolysosomal destabilization [32][33][34] and, in some circumstances, lead to cell death. Incubation of mononuclear cells with apatite for long periods could therefore result in artefactual particle 'gorging', lysosomal disruption and cell death [2].…”
Section: Effect Of Resting Of Cells and Tcm Filtrationmentioning
confidence: 99%
“…Furthermore, calvarial bone resorption that is induced by polymethylmethacrylate (PMMA) particles is reduced in the absence of NLRP3 (143). The size and shape of metal alloys affect the amplitude of the inflammasome response (144). Plastic components of the prostheses also activate the inflammasome.…”
Section: Figure 2 the Inflammasomes In Osteolysismentioning
confidence: 99%
“…Finally, in addition to metal ions, various studies have shown that larger (around one micron sized) metal particles of various materials can directly activate macrophages and other cells in a similar manner that has been described for polyethylene and PMMA wear debris, such as direct recognition of protein coated particles by various pattern recognition receptors as well as by particle phagocytosis followed by endosomal damage and activation of intracellular danger signal mechanisms 78 , 90 , 154-156 .…”
Section: Challengesmentioning
confidence: 78%